PENERAPAN SAP (SYSTEM ANALYSIS AND PRODUCT IN DATA PROCESSING) BERBASIS ICT PADA AKUNTABILITAS LAPORAN KEUANGAN PERUM LPPNPI CABANG SURABAYA - Dara Nursyifa Sofian; Rika Yuliastuti (PUTRA JAWA PUBLISHER, 2024)
The primary goal of this research is to investigate the effectiveness of using System Analysis and Product in Data Processing (SAP) in enhancing the accountability and transparency of financial reports, as well as improving the accuracy of these reports. To achieve this objective, a qualitative approach was employed, involving interviews with employees as the primary method of data collection. The study was carried out within the Finance Unit of Perum LPPNPI Surabaya Branch, where SAP has been successfully implemented. The findings from the research indicated that the integration of SAP has positively impacted the accountability of financial statements and has contributed to enhancing the transparency of these reports.